2019
DOI: 10.1038/s41598-019-47962-3
|View full text |Cite
|
Sign up to set email alerts
|

Cucumber mosaic virus-induced gene silencing in banana

Abstract: Banana ( Musa spp.) is one of the world’s most important staple and cash crops. Despite accumulating genetic and transcriptomic data, low transformation efficiency in agronomically important Musa spp. render translational researches in banana difficult by using conventional knockout approaches. To develop tools for translational research in bananas, we developed a virus induced-gene silencing (VIGS) system based on a banana-infecting cucumber mosaic virus (CMV) iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 65 publications
0
18
0
Order By: Relevance
“…Virus-induced gene silencing (VIGS) can be used to analyze gene function via the transient silencing of RNA expression; VIGS thus compensates for the time-consuming and inefficient nature of transgenic banana production ( Baulcombe, 1999 ). For example, Tzean et al (2019) developed a VIGS system based on a banana-infecting cucumber mosaic virus (CMV) to efficiently silence target genes. This system might be useful for gene functional analysis in bananas before stable genetic transformation.…”
Section: Gene Editing Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Virus-induced gene silencing (VIGS) can be used to analyze gene function via the transient silencing of RNA expression; VIGS thus compensates for the time-consuming and inefficient nature of transgenic banana production ( Baulcombe, 1999 ). For example, Tzean et al (2019) developed a VIGS system based on a banana-infecting cucumber mosaic virus (CMV) to efficiently silence target genes. This system might be useful for gene functional analysis in bananas before stable genetic transformation.…”
Section: Gene Editing Systemsmentioning
confidence: 99%
“…Because bananas are nutritious and starchy, they are considered the fourth most important food crop after rice, wheat, and maize for the alleviation of human starvation in Africa by the United Nations Food and Agriculture Organization ( Song et al, 2018 ). In 2019, worldwide banana production was over 113 million tons; the two largest producers of bananas are India (36.7%) and China (13.8%) ( Tzean et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…CMV has been developed as a useful VIGS vector for many plants including Nicotiana benthamiana, tomato, pepper, Arabidopsis thaliana, lily, soybean, banana and maize (Hong et al 2012;Liu et al 2010;Otagaki et al 2006;Tzean et al 2019;Wang et al 2016). Recently, it has been demonstrated that we could silence even a gene of mycorrhizal fungi that colonized the root of N. benthamiana (Kikuchi et al 2016).…”
Section: Short Communicationmentioning
confidence: 99%
“…Given these features, VIGS is an attractive reverse genetic tool for functional genomics in plants [ 4 8 ]. In the past decade, a number of viral genomes has been modified as a powerful reverse genetic tool for the functional characterization of genes in plants, such as Tobacco rattle virus [ 9 ], Apple latent spherical virus [ 10 , 11 ], African cassava mosaic virus [ 12 ], and Cucumber mosaic virus [ 13 ]. However, most of the reported VIGS vectors only silence a single gene, and the VIGS vectors with visualizable indicator to evaluate the early penetrance of genes for reverse genetics are lacking.…”
Section: Introductionmentioning
confidence: 99%